Students' Numeracy Literacy Using Artificial Intelligence (AI)-Based Worksheets - Agustiani, Riza; Zahra, Atika; Putri, Agustiany Dumeva; Hadi, Muhammad; Marwan, Aji; Solehah, Asna Markhotun; Saputri, Anggun Meylani; Sopani, Ahmad (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2024)
Artificial Intelligence has significant potential to enhance the mathematics learning experience. To fully realize the benefits of AI integration, it is crucial to develop teaching materials that effectively incorporate AI into classroom instruction. This study focuses on developing AI-based student worksheets to improve numeracy literacy skills among junior high school students. These worksheets were created with the support of AI technology and include AI applications that can be used directly during the learning process. Conducted in state junior high schools (SMP) and Islamic junior high schools (MTs) in Palembang, the project followed a series of formative evaluation stages. These stages involved self-evaluation, expert reviews, one-on-one sessions, small group testing, and field testing, alongside product dissemination activities. Data on students' numeracy literacy skills were gathered through interviews and tests, while the analysis process consisted of three key stages: data reduction, data presentation, and drawing conclusions. The findings showed that some students had already grasped the steps to solve problems. Overall, the evaluation results for the numeracy literacy test were categorized as high performance. The AI-based worksheets proved effective in helping teachers deliver engaging teaching materials and enhancing students' learning experiences, particularly in improving their numeracy literacy.